Pain, physiological alterations and analgesia in patients submitted to medium-sized surgeries - Barbosa, Maria Helena (2014)
The objectives of this study were to evaluate pain intensity in postoperative patients, identify associations between physiological alterations and the presence of pain, and describe the analgesia used. This qualitative, longitudinal study was performed in a public teaching hospital by evaluating pain, physiological alterations and analgesic scheme of 351 patients in three postoperative moments following medium-sized surgeries. Descriptive analysis of the absolute and percentile frequencies was performed. The Chi-squared and Bonferroni’s tests were used to verify associations and variances. The occurrence of pain reduced with time in the postoperative period. Mild pain prevailed. The physiological alterations declined and were associated with pain in every moment of the studied period. Regarding analgesia, the fixed time scheme combined with the use of non-steroidal anti-inflammatory drugs, simple analgesics and opioids were the most used. In conclusion, this type of analgesia helps to manage pain, which is associated with the presence of physiological alterations. Descriptors: Pain, Postoperative; Pain Measurement; Analgesia; Pain Management; Nursing Care.